Shedding light on the effect of saturated aldehydes and alcohols in Rhizobium cells challenged by cadmium: growth and biochemistry - Matos, Diana Rita Silva (2019)
Rhizobia are soil bacteria that play significant agronomic and environmental roles and are decisive contributors to soil fertility. However, these microorganisms are affected by environmental stresses such as cadmium contamination, which alters the metabolism of organisms, including bacterial volatilome (a set of metabolites synthesized by an organism). Two groups of compounds that change in cadmium-exposed rhizobia cells are saturated aldehydes and alcohols, yet the effect of these compounds on bacterial cells is poorly known. In this thesis the effects of different aldehydes (hexanal, heptanal, octanal, nonanal, decanal, undecanal, dodecanal and tridecanal) and alcohols (hexanol, heptanol, octanol and nonanol) separately or in combination with cadmium on growth and biochemistry of Rhizobium cells (strain E20-8) are evaluated. Results show that smaller aldehydes (6 to 10 carbons) reduced lipid peroxidation (37% to 50%), while larger aldehydes (11 to 13 carbons) increased it slightly (20% and 30%) or significantly (> 70%), showing the protective function of the smaller aldehydes and the destabilizing effect of the largest ones in membranes. Enzymes with antioxidant activity such as superoxide dismutase decreased in the presence of smaller aldehydes and increased in the presence of larger ones, showing the activation of antioxidant mechanisms in cells exposed to larger aldehydes. Exposure to different aldehydes did not influence Rhizobium cell growth in most of the conditions tested, either in the presence or absence of Cd. However, exposure to 1mM decanal and 10 μM tridecanal caused a significant increase in Cd growth. The comparison of aldehydes with their conjugated alcohols effects on Rhizobium cells exposed or not to Cd allowed to elucidate which of the two types of compounds was more toxic to cells. Results showed the higher toxicity of most aldehydes compared to their conjugated alcohol in the presence of Cd, suggesting that reduction of aldehydes to alcohols may be an effective mechanism of aldehyde toxicity restriction. This thesis presents new information that helps clarify the changes occurring in bacterial cells exposed to Cd and the cell-induced mechanisms to minimize this toxicity. The contribution is especially relevant in influence that these compounds may have in the protection of bacterial communities under environmental stress contexts.